TRANSFORMATION OF ENVIRONMENTALLY FRIENDLY SCHOOLS THROUGH THE INTEGRATION OF GREEN TECHNOLOGIES AND SUSTAINABLE MATERIALS: A LITERATURE REVIEW - Habel Wilefri Al Hadad; Nurhasan Syah; Rusnardi Rahmat Putra; Muhammad Akbar (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
The purpose of this research is to examine the influence of implementing green technology and sustainable materials in the development process of environmentally friendly schools and their impact on the learning environment and educational achievement. This study applies a qualitative Systematic Literature Review methodology. To systematically integrate the scientific literature, narrative synthesis and thematic analysis methods are employed. Based on the analysis results, it can be stated that green technology plays a highly important role in improving energy efficiency and indoor environmental quality, while sustainable materials provide a significant contribution to reducing environmental impacts throughout the building life cycle. The combination of these two elements is capable of enhancing thermal comfort, air quality, and natural lighting, which positively affect students’ ability to concentrate, think critically, and support the creation of a more effective and healthier learning process. In this context, the research emphasizes the importance of an integrated approach in designing school buildings that simultaneously considers green technology and sustainable materials in order to create an environmentally friendly, sustainable educational environment that supports the improvement of students’ learning quality.